2015
DOI: 10.1532/hsf.1252
|View full text |Cite
|
Sign up to set email alerts
|

The St. Jude Toronto stentless bioprosthesis: Up to 20 years follow-up in younger patients

Abstract: In younger patients the Toronto-bioprosthesis provided reliable long-term survival despite limited durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Studies on valve performance during the first decade following valve replacement have reported that structural valve deterioration occur in ≤15% during the first decade post-AV replacement, but its incidence progressively increases thereafter. [26][27][28][29] However, it is known that in young patients the durability of a bioprosthetic valve is not as good as in older patients. In their study, Al-Khaja et al 30 showed that at a mean follow-up of 7.5 years, the reoperation rate of patients younger than 40 years of age was 59%, in patients aged 40-49 the reoperation rate was 44%, and in those aged 50-59, the reoperation rate was 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on valve performance during the first decade following valve replacement have reported that structural valve deterioration occur in ≤15% during the first decade post-AV replacement, but its incidence progressively increases thereafter. [26][27][28][29] However, it is known that in young patients the durability of a bioprosthetic valve is not as good as in older patients. In their study, Al-Khaja et al 30 showed that at a mean follow-up of 7.5 years, the reoperation rate of patients younger than 40 years of age was 59%, in patients aged 40-49 the reoperation rate was 44%, and in those aged 50-59, the reoperation rate was 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Current data on the durability of bAVR show a non-linear trend with an inflection point beyond 6 years after operation [ 16 ]. Studies on valve performance have reported rates of freedom from SVD at 10 years up to 85% [ [17] , [18] , [19] , [20] ]. Bourguignon and colleagues [ 5 ] reported excellent long-term valve durability of 17.6 years, with 15/20 years freedom from SVD of 66.8%/38.1%, for patients aged 60 years or younger (median age 54, IQR: 47–57.5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the encouraging performance of surgical bioprostheses in the first-decade post-surgery with freedom from SVD in > 85% at 10 years. 26,[34][35][36][37] Recent data from the SWEDEHEART registry reported a median survival of 16.2 years (ages 60-64 years) to 6.1 years (age > 85 years) in low-risk patients undergoing bioprosthetic SAVR for severe aortic stenosis. 37 Historically, structural valve degeneration was defined using clinical end points such as valve reintervention or death related to structural valve failure rather than long-term echocardiographic and hemodynamic assessment.…”
Section: Caveats Of Savr Durability Assessmentmentioning
confidence: 99%